A practical velocity-based method for signal reproduction control in shaking table tests. (June 2023) - Liu, Zhi-Qian; Chen, Zhi-Yi; Yang, Cheng-Yu; Huang, Peng-Fei
Abstract: Accurate reproduction of ground motion time histories with different frequency characteristics is one of the core issues in shaking table tests. Acceleration-based signal reproduction control method (Acceleration-based SRCM), which adopts the acceleration as the primary reference signal for reproducing ground motion time histories, is now widely applied in various shaking table tests. However, due to the performance limitations of the electro-hydraulic system and the low sensitivity of the acceleration signal in the low-frequency band, taking the acceleration as the reference signal may lead to poor reproduction accuracy of ground motions with rich low-frequency components and containing velocity pulses, thus resulting in inaccurate response results of test model systems. To improve the accuracy of the reproduced ground motion in the low-frequency band, a new reproduction control method, Velocity-based SRCM, which adopts the velocity as the reference signal, is explored in this paper, which avoids the high-pass filtering in the acceleration-velocity integration process of the three-variable signal generator. Velocity-based SRCM is tested and compared with Acceleration-based SRCM by the multifunctional shaking table system at Tongji University. The results demonstrated that Velocity-based SRCM improved the accuracy of the low-frequency components below 1.0 Hz in the reproduced signals. Finally, based on the test results, the ground motion intensity and the ratio Tm / Tc are suggested as the identification basis, and a general recommendation for selecting the reproduction method is given.